Effectiveness and Safety of Medical Abortion with Mifepristone and Sublingual Misoprostol up to 63 Days of Gestation - Prakasit Saengbanyang; Thanyarat Wongwananuruk; Nalinee Panichyawat; Natchara Sukapatrittikul Powell; Nichamon Parkpinyo (IMR Press, 2024)
Background: The use of medical abortion increases among unplanned pregnant women. The primary objective of this study is to assess the outcomes of using a combination of Mifepristone followed by sublingual Misoprostol for the termination of pregnancy up to 63 gestational days. The secondary objectives were identifying significant factors that contribute to an increased rate of incomplete abortions resulting in surgical intervention and evaluating the safety of this medical procedure. Methods: This retrospective cohort study was conducted at Siriraj Hospital, a tertiary care center in Thailand, from July 2021 to December 2023. Women were given 200 mg of oral Mifepristone at the clinic, followed by self-administration of 800 μg of sublingual Misoprostol at home 36-48 hours later. A follow-up visit was scheduled approximately 14 days later to confirm the outcome of the procedure. Demographic and medical data were collected from medical records and subsequently analyzed. The primary outcome was defined as the success of the procedure, indicated by complete abortion without the need for surgical intervention. Secondary outcomes included assessing side effects and complications following medication administration, as well as identifying factors associated with an increased rate of incomplete abortions. Results: The final analysis included follow-up data from 205 women. Medical abortion was successful in 70.7% (145 out of 205) of cases, with no ongoing pregancies recorded. No serious side effects or complications were detected. Diarrhea and chills were the most commonly observed side effects. The study found that women with a history of previous abortions and those experiencing significantly heavier bleeding after the procedure were at a higher risk of incomplete abortion, requiring surgical aspiration. Conclusions: The regimen of oral Mifepristone followed by sublingual Misoprostol for medical termination of pregnancy is effective and safe through 63 days of gestation. A history of previous abortion and experiencing heavier bleeding after the procedure were identified as risk factors for incomplete abortion.